The importance of oxidative stress in the pathogenesis and treatment of bipolar affective disorder: a review of the literature - Łobejko, Łukasz; Hordejuk, Michalina; Róg, Joanna; Karakuła-Juchnowicz, Hanna (Current Problems of Psychiatry, 2024)
Introduction: Bipolar affective disorder (BD), also known as manic-depressive illness, is a chronic and recurrent psychiatric disorder characterised by significant mood disturbances. It is one of the leading causes of disability worldwide and is associated with a high risk of suicide. Recent studies highlight the role of oxidative stress (OS) in the pathogenesis of BD. The body's pro/antioxidant imbalance adversely affects cellular and molecular processes.Aim: The aim of this review is to synthesise the current state of knowledge on the role of OS in the aetiology and course of BD, including key biomarkers and potential therapeutic interventions.Methods: A review of the scientific literature was conducted, including articles published between 2000 and 2024. Searches were conducted in PubMed, Scopus and Web of Science databases, using the following keywords: 'bipolar disorder', 'oxidative stress', 'antioxidants', 'biomarkers', 'mitochondrial dysfunction', 'redox homeostasis', 'treatment'.Results: Results indicate that patients with BD have elevated levels of OS markers, including increased lipid peroxidation, altered antioxidant enzyme activity and impaired redox homeostasis. Treatment with lithium and other mood stabilisers may modulate levels of OS markers, which is one potential mechanism of drug action. However, inconclusive data suggest the need for further research to clarify the relationship between OS and BD.Conclusions: OS plays an important role in the pathophysiology of BD, offering potential directions for therapeutic interventions. Understanding the complex interactions between OS and BD may lead to the development of more targeted therapies aimed at reducing oxidative damage and improving patient health.